2016
DOI: 10.1002/ppul.23427
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar ventilation in children during flexible bronchoscopy

Abstract: A large proportion of children undergoing FB have significant alveolar hypoventilation indicated by a rise in TcCO . Monitoring ventilation with TcCO is feasible and should be added during FB particularly in cases that are expected to require large amounts of sedation and patients susceptible to complications from respiratory acidosis. Pediatr Pulmonol. 2016;51:1177-1182. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Similar data were also found in the pediatric population showing alveolar hypoventilation during flexible bronchoscopy particularly in cases requiring large amounts of sedation and in patients susceptible to complications from respiratory acidosis (8).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Similar data were also found in the pediatric population showing alveolar hypoventilation during flexible bronchoscopy particularly in cases requiring large amounts of sedation and in patients susceptible to complications from respiratory acidosis (8).…”
supporting
confidence: 72%
“…Different kind of bronchodilator agents were tested, such as a combination of β2-short acting and anticholinergic drugs, administered either topically and systemically (8)(9)(10)(11). Therefore, the administration of nebulized bronchodilators has been requested before flexible bronchoscopy in asthmatic patients (12).…”
mentioning
confidence: 99%
“…Once a bronchoscope is introduced through an ETT, the decreased effective diameter for gas exchange is associated with reductions in airflow and resultant alveolar hypoventilation. [ 100 ] This may be countered through bronchoscopy through a laryngeal mask airway or by the administration of helium along with oxygen, as the lower density of helium allows for decreased resistance to air movement. [ 19 101 ] Although rigid bronchoscopes do offer a means for ventilation through the hollow interior, the turbulent nature of flow through the bronchoscope significantly increases resistance in comparison to an ETT of a similar diameter.…”
Section: Intraoperative Anesthetic Care For Specific Diagnostic and Surgical Proceduresmentioning
confidence: 99%
“…Sadot et al point to a potential risk when performing bronchoscopy in children during spontaneous breathing: when only transcutaneous arterial oxygen saturations are monitored during the procedure, particularly when oxygen is concomitantly administered, alveolar hypoventilation may occur and remain undetected. The authors reported an increase in transcutaneously measured CO 2 (TcCO 2 ), with a median rise of 17 mm Hg during the procedure, and 55% of patients experiencing a rise of more than 15 mm Hg.…”
Section: Diagnostic Testing/endoscopymentioning
confidence: 99%